Correlation of Maternal Neck/Waist Circumferences and Fetal Macrosomia in Low-Risk Turkish Pregnant Women, a Preliminary Study. (20th May 2021) - Hancerliogullari, Necati; Kansu-Celik, Hatice; Asli Oskovi Kaplan, Z.; Oksuzoglu, Aysegul; Ozgu-Erdinc, A. Seval; Engin-Ustun, Yaprak
Abstract: Goals: Our aim in this study was to determine if the maternal neck and waist circumference measured in the first three months of pregnancy were effective in prediction of fetal macrosomia. Material and methods In this retrospective cohort study; body mass index, neck circumference (NC) and waist circumference (WC) was measured in low risk pregnant women at 11–13+ 6th weeks of pregnancy. Results Among the 361 women, 8% of newborns were over 4000 grams. The rate of fetal macrosomia increased with the increased NC and WC. In ROC analysis, optimum cutoff value of NC was >36.5 cm to predict fetal macrosomia with 68.97% sensitivity and 66.97% specifity and for WC it was >88 cm with 62.07% sensitivity and 61.26% specifity. Conclusion Risk of fetal macrosomia increased with the increased maternal NC and WC.